A practical approach to hazard identification for operations and maintenance workers (Wiley, 2010)
The first part of this book (Chapters 1 and 2) provides an introduction and discusses basic concepts. Chapter 3 deals with the use of the basic human senses for identifying hazards. Chapter 4 deals with different classes and categories of hazards. Chapter 5 deals with techniques and methodologies for identifying and evaluating hazards. Chapter 6 deals with making risk based decisions. Chapter 7 deals with follow-up and call to action. Chapter 8 deals with learning and continuous improvement. The Appendices provide references, case studies, hazard presentations and additional pic.